2018
DOI: 10.1002/micr.30349
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of plate extrusion in oromandibular free flap reconstruction

Abstract: At our institution, use of the STFF predicts mandibular defects that are less prone to developing plate extrusion and FFF tended to be used more frequently in anterior defects with osteotomies. However, after controlling for these factors use of the FFF appeared to have higher rates of extrusion than scapular flaps. Further prospective studies controlling for defect variables are needed to elucidate the risk factors for plate extrusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
(66 reference statements)
1
27
0
1
Order By: Relevance
“…Oromandibular reconstruction is well-established, and the scapula, fibula, and radial forearm are workhorse osseous flaps that provide good form and function for speech, swallowing, mastication, aesthetics, and oral competence. 1 Over the last decade, there have been various studies 12,16,17,[20][21][22] that have identified common postoperative complications and potential predictors of these complications following oromandibular reconstruction with the goal of optimizing surgical outcomes. It is known that early and late complications after oromandibular reconstruction are common.…”
Section: Discussionmentioning
confidence: 99%
“…Oromandibular reconstruction is well-established, and the scapula, fibula, and radial forearm are workhorse osseous flaps that provide good form and function for speech, swallowing, mastication, aesthetics, and oral competence. 1 Over the last decade, there have been various studies 12,16,17,[20][21][22] that have identified common postoperative complications and potential predictors of these complications following oromandibular reconstruction with the goal of optimizing surgical outcomes. It is known that early and late complications after oromandibular reconstruction are common.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our clinical outcome was comparable with previous reports (Arden et al, ; Fanzio et al, ; Maurer et al, ; Okura et al, ). In various studies, many predictive factors have been presented, and physical factors (Fanzio et al, ; Maurer et al, ; van der Rijt et al, ; Wood et al, ), hardware factors (Arden et al, ; Ettl et al, ; Mariani et al, ; Okura et al, ; Poli et al, ; Prasad et al, ; Shibahara et al, ), and treatment factors (Okura et al, ; Ryu et al, ; Shibahara et al, ; Wang et al, ) have been reported. Among these factors, plate length and the location of a mandibular defect influenced the prognosis of plate survival.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis (Sadr-Eshkevari et al, 2013) demonstrated that the failure rate was 30.8% at the 32-month follow-up and discussed the risk factors of reconstruction plate failure from various viewpoints. Many reports discuss the influencing factors for reconstruction plate survival and list many factors such as physical factors such as whether an individual has diabetes mellitus (van der Rijt et al, 2015), smoking habit (Maurer et al, 2010;van der Rijt et al, 2015), whether an individual has had a blood transfusion (Fanzio et al, 2015), and surgical infection site (Wood, Shinn, Amin, Rohde, & Sinard, 2018), hardware factors such as plate length and location of a mandibular defect (Arden, Rachel, Marks, & Dang, 1999;Ettl et al, 2010;Mariani, Kowalski, & Magrin, 2006;Okura, Isomura, Iida, & Kogo, 2005;Poli, Ferrari, Bianchi, & Sesenna, 2003;Prasad et al, 2018;Shibahara, Noma, Furuya, & Takaki, 2002), and treatment factors such as radiation therapy and chemotherapy (Okura et al, 2005;Ryu et al, 1995;Shibahara et al, 2002;Wang, Zhang, & Mendenhall, 2005). Most reports have focused on the shape of the mandibular bone defect after resection and hardware-related complications; however, few reports have analyzed risk factors for plate failure from the viewpoint of dental occlusion (i.e., the mechanical force exerted on the reconstructed mandible and plate).…”
mentioning
confidence: 99%
“…Variables previously demonstrated to be associated with hardware complications were considered for inclusion in the multivariable logistic regression model for each outcome. For plate exposure, these included age, smoking, radiation therapy, plate profile height, classification of defect, flap type, and surgical site infection 2,3,7,10,15 . For the composite outcome, these included age, smoking, diabetes, radiation therapy, plate profile height, classification of defect, flap type, and surgical site infection 2,3,7,10,15 .…”
Section: Methodsmentioning
confidence: 99%
“…Reconstruction hardware can be associated with complications including infection, plate exposure, plate fractures, and screw loosening. The rates of hardware‐related complications are variably reported (3%–45%) and may require prolonged treatment with antibiotic therapy and occasionally revision surgery to remove or replace the hardware 2–13 …”
Section: Introductionmentioning
confidence: 99%